Development and Standardization of an Alienation Scale for Visually Impaired Students. (September 2017) - Punia, Poonam; Berwal, Sandeep
Introduction: The present study was undertaken to develop a valid and reliable scale for measuring a feeling of alienation in students with visual impairments (that is, those who are blind or have low vision). Methods: In this study, a pool of 60 items was generated to develop an Alienation Scale for Visually Impaired Students (AL-VI) based on a review of the literature and discussions with colleagues and experts in the field. The items were organized into six dimensions of alienation, namely powerlessness, meaninglessness, normlessness, social isolation, self-estrangement, and cultural estrangement, and were rated on the five-point Likert scale. The standardization of the scale was completed with 118 students with visual impairments in the age group of 10 to 25 years, selected randomly from specialized and inclusive schools in the state of Haryana, India. Results: The item analysis was done by calculating t - and r -values; seven items were deleted, and a final 45 items were retained. The calculated value of Cronbach's alpha and split-half correlation came out to be 0.87 and 0.86, respectively. The construct validity was determined by computing the coefficient of correlation between scores of this scale and the scores obtained by using the Student Alienation scale (SAS) of R. R. Sharma (Sharma, 2012). The percentile norm for the scale was determined after verifying normality of the scores by using a Q-Q plot. Discussion: The findings of the present study suggest that the AL-VI may serve as a useful tool in future research to assess alienation in persons with visual impairments in India. The findings further demonstrate that the AL-VI produced scores that are reliable and valid. The AL-VI can be used outside India after determining its reliability and validity in context-specific conditions. Implications for practitioners: The AL-VI scale is applicable to students with visual impairments, teachers of students with visual impairments, principals, social workers, psychologists, and rehabilitation professionals. Practitioners could use this tool for assessing and understanding the level of alienation among students with visual impairments, thereby helping them in planning and executing strategies for remediating alienation.